Why women kill. Season one [videorecording (DVD)] - Hamilton, Mary Elizabeth; Liu, Lucy, 1968-; Goodwin, Ginnifer; Howell-Baptiste, Kirby; Daddario, Alexandra, 1986- (Why women kill (Television series), 2020)
It details the lives of three women living in three different decades: a housewife in the '60s, a socialite in the '80s, and a lawyer in 2018, each dealing with infidelity in their marriages. The series will examine how the roles of women have changed, but how their reaction to betrayal, has not.